Psychological Characteristics of Explication of Narration and Time in Graphic Novels - Ernest Ivashkevych (Проблеми сучасної психології, 2020)
The purpose of our article is to describe various narrative devices of the comic book which can also enable the reader to identify to the characters in a new way by concretely positioning the reader inside the point of view of a certain character, and, on its basis to propose psycholinguistic aspects of narrative discourse. Methods of the research. The following theoretical methods of the research were used to solve the tasks formulated in the article: a categorical method, structural and functional methods, the methods of the analysis, systematization, modeling, generalization. The results of the research. It was underlined that the important part of comic book narration was also the point of view: who was watching and what was the object of this gaze; if a character was following something and in the next panel we were shown this object of the gaze, the reader would be positioned as this character. This type of positioning is essential in comic book narration, as it has the possibility of affecting the meanings linked with the reading of the comics. It was described the role of visual images, which helped the reader to understand the textual information. Through repetition the visual images become symbols, which mean that they begin to represent something else through a rule or a shared agreement. These symbols become narrative, and act as parts of the narrative by the way of integrating the symbolic meanings linked to them to new contexts. The symbols can even turn into metaphors, as for example the recurring image of the Comedian being flung through the window, which may be interpreted as speaking of the violence hidden in all of us. It was shown that the type of transformation of visual information was familiar from film studies, and it was a clearly visual way of narrating the past private experiences of the character through external focalization, showing what the character had experienced in the past but from outside the character. Still, while reading the novel it is easy to notice how the use of visual elements to provide smooth transitional moments in space and time is a practical advantage of a rich visual style that exceeds the content of the words. This playing with temporal levels and transitional moments in time and space is in fact an essential quality of the narrative of «Watchmen», leading to the interpretation that alongside power, time is one of the crucial overall themes of the graphic novel. Conclusions. Analyzing «Watchmen», the author of this article proposed such psycholinguistic aspects of narrative discourse, as: visual emphasis; focalization of information; epigraphs’ emphasis; meta-narrative presentation of the text; contrasting visual linkings; actualization of narrative potential. It was shown that the panel arrangement can deceive the reader, too. Various types of temporal situations that bear on our judgments of causality may be created through the juxtaposition of spatial fragments from different shots. In several storylines within «Watchmen», two parallel narratives are presented to the reader in juxtaposition, happening simultaneously, so that a parallel is drawn between them like in many other instances in the comic.